The Role of Non-reductive Naturalism: Cognitive Science or Phenomenology?. Issue 2 (3rd April 2018) - Sachs, Carl B.
Abstract: Shaun Gallagher argues that we need a new philosophy of nature that accommodates the insights of existential phenomenology. On his view existential phenomenology needs a philosophy of nature that is holistic, relational, and non-reductionist. I argue that his reasoning is based on a misunderstanding of the difference between the manifest image and the scientific image. The reasons why we should prefer a non-reductionist philosophy of nature are internal to the historical development of the scientific image itself. We have good reasons for preferring enactivism over cognitivism as a research program for the cognitive sciences, but compatibility with the manifest image is not one of those reasons.